Strategy For Increasing Financial Accountability In Wakaf Management In Islamic Religious Organizations In North Sumatera - Nurhudawi, Nurhudawi; Zein, Aliman Syahuri; Hardana, Ali (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
Accountability is a process by which an institution holds itself responsible for what it does. Accountability is not solely related to financial reporting and programs made, but also related to public legitimacy. This study aims to determine the priority of problems and solutions as well as to offer appropriate strategies for increasing financial accountability in Islamic Religious organizations in North Sumatra. This type of research uses the Analytic Network Process (ANP) method approach and the help of Super Decision software. The number of respondents in this study amounted to 11 people consisting of three academics, four regulators, and four practitioners. The results showed that according to the respondents, the priority of financial accountability issues was that financial transparency was still low, the second priority was that Nazir had not been able to prepare reports according to standards and the third priority was that the use of reporting information systems was still low. The priority solution is training in preparing financial reports for Nazir, the second priority solution is an audit and the third priority is supervision of the implementation of information systems. According to all respondents, the strategic priority is synergy between regulators, Nazirs, and mass organizations. Furthermore, the second priority is the waqf management training strategy for Nazirs. The last priority is the strategy for making a waqf development master plan.